The Licochalcone A induces tegumental damages in Schistosoma mansoni and impairs its oviposition in vitro - Felicissimo, Juliane Marques; Marconato, Danielle Gomes; Emídio, Nayara Braga; Carvalho, Lara Soares Aleixo de; Fontes, Lívia Beatriz Almeida; Couto, Flávia Fernanda Bubula; Araújo, Neusa; Vasconcelos, Eveline Gomes; Moraes, Josué de; Pinto, Pedro Luiz Silva; Silva Filho, Ademar Alves da; Pinto, Priscila de Faria (Brazilian Journal of Veterinary Pathology, 2021)
In this study, Licochalcone A (LicoA) was investigated in in vitro and in vivo assays. The survival of worms in culture, the pattern of oviposition, the count of intact tubers and the integrity of the coat were adopted in the in vitro tests. After the animals were perfused, the number of worms recovered, their location and the oogram study were the parameters analyzed to signal the existence of potential schistosomicidal activity in vivo. We observed reduction on the survival, integument integrity and reproduction of adult worms in vitro. Murine models did not show a significant difference in the parasitological parameters analyzed that indicate activity against the worms with an oral single dose of 25 mg/ kg of LicoA or two intraperitoneal injection of 50 mg/ kg LicoA. Nevertheless, it is too early to completely exclude the schistosomicide activity of LicoA, considering that the used dosage form could not provide a regular absorption of the drug.